Oscillatory biomarkers of early auditory information processing predict cognitive gains following targeted cognitive training in schizophrenia patients - Hochberger, William C. (Schizophr Res, 2019)
Auditory-based targeted cognitive training (TCT) is an effective and well-validated intervention for the treatment of cognitive impairment in schizophrenia patients. Improvements in higher-order cognition, reductions in symptom severity, and increases in psychosocial functioning secondary to TCT are thought to be driven by “bottom-up” enhancement of early auditory information processing (EAIP). Despite strong evidence of efficacy at the group level, there is significant variability in response to TCT, with few well-delineated biomarkers for predicting individual benefit. EEG biomarkers of EAIP are indicators of early-treatment sensitivity that predict full-course TCT outcome; however, further characterization is necessary for biomarker-guided clinical trials. The current study examined baseline and early-treatment sensitivity (i.e., change from baseline after 1hr) in theta band oscillatory activity to deviant stimuli as moderators of full course (30hr) TCT response in treatment-refractory schizophrenia patients randomly assigned to receive either treatment-as-usual (TAU; n = 22) or TAU augmented with TCT (n = 30). Theta evoked power and phase locking at baseline predicted patient improvements in global cognitive function after 30h of TCT. Decrease in theta activity to deviant stimuli after 1h of TCT predicted improvements in verbal learning after 30h. Exploratory analyses using EEG composite scores had high levels of sensitivity and specificity for identifying patients most likely to benefit from TCT. The integrity of baseline neurophysiologic activity associated with EAIP, as well as the sensitivity of the underlying circuity to change, likely reflects an intermediate therapeutic process underlying the effectiveness of TCT that can be used to predict patient response to treatment.